Alternative tools to mass production and human performance indicators in sheltered work centers of Valencian community (Spain) - Juan A. Marin-Garcia; Cristobal Miralles; Julio J. Garcia-Sabater; M. Rosario Perello-Marin (Journal of Industrial Engineering and Management, 2011)
Purpose: The most popular alternative systems to mass production at an academic level (lean manufacturing, agile manufacturing, flexible customization, mass customization...) share many characteristics. Our article identifies an extensive set of alternative practices to mass production; analyzes the classification of practices in categories (Flow, TQM, TPM, Customer Relations, Supplier Relations and Human Resources Practices) and analyzes the impact on several human performance indicators such as satisfaction, absenteeism, voluntary turnover, permanent contracts, knowledge, personal & social adjustment activities and integration of workers into ordinary companies. Design/methodology/approach: Survey in sheltered work centers. We use regression analysis in order to prove relations between explicative and criterion variables. Findings: The results of our research allow us to identify that human resource management and customer relationship practices have significant effects on job satisfaction, knowledge, integration into ordinary companies and personal and social adjustment. Research limitations/implications: Data came only from one industry; therefore the results would not be directly generalized to other contexts. Practical implications: Managers in Sheltered work centers can estimate the impact of the deployment of alternative tools to mass production. Originality/value: There are few papers relating lean manufacturing tools and human resources performance indicators. At the same time, there are very few research carried out in sheltered work centers context.